(untitled) (Baghdad Science Journal, 2025)
The studies on the antiviral compound chalcone in vitro in both tissue and organ culture systems against rubella virus glass that this compound relatively non toxic to the cell culture and organ culture of the concentration of 8 ug/ml or less, chalcone have significantly antiviral activity against rubella virus in tissue culture and organ culture. We find that a concentration of 0.03ug/ml or more inhibit the IOOTCID50 of rubella virus. The therapeutic index (TI) used in this study to evaluate the drug, the (TI) which is the ratio of the dose of drug which is just toxic (Maximum tolerated dose) to the dose which is just effective (Minimum effective dose). If this index is one or less it not possible to use the drug under the conditions outlined without causing side effect, if the index is larger than the margin of safety is accordingly great, the TI of chalcone against rubella virus more than 70, therefore this compound if used in man have no side effect .